A systematic review of the clinical validity and clinical utility of DNA testing for hereditary haemochromatosis type 1 in at-risk populations. Issue 8 (29th February 2008) - Bryant, J; Cooper, K; Picot, J; Clegg, A; Roderick, P; Rosenberg, W; Patch, C
Abstract : Objective: To evaluate the clinical validity and clinical utility of DNA testing in people suspected of having hereditary haemochromatosis and in family members of those diagnosed with the disorder. Design: A systematic review. Methods: 15 electronic databases were searched up to April 2007. For assessment of the clinical validity of genotyping for the C282Y mutation in the diagnosis of hereditary haemochromatosis, studies were included if they reported the use of DNA tests in Caucasians of northern European origin with iron overload suggestive of haemochromatosis compared with a control population, and reported or allowed calculation of sensitivity and specificity. For clinical utility, studies were included if participants were Caucasians with iron overload suggestive of haemochromatosis or were relatives of suspected cases, if the study compared a diagnostic strategy incorporating DNA testing with one not incorporating DNA testing, and if the study reported patient-based outcomes or some measure of cost effectiveness. Results: 11 studies that could be used to evaluate clinical validity of genotyping for the C282Y mutation in the diagnosis of hereditary haemochromatosis were identified. Clinical sensitivity of C282Y homozygosity for hereditary haemochromatosis ranged from 28.4% to 100%; when considering studies that used strict criteria to classify hereditary haemochromatosis clinical sensitivity ranged from 91.3% to 92.4%. No clinical effectiveness studies were found. Two cost effectiveness studies were identified, both of which suggested that gene testing may be cost effective. Conclusion: DNA testing for hereditary haemochromatosis in at-risk populations has clinical validity and may have clinical utility. The review highlights the limitations of the literature and the methodological difficulties associated with evaluating this genetic test.